2018
DOI: 10.5152/iao.2018.5442
|View full text |Cite
|
Sign up to set email alerts
|

Association between Uncoupling Protein 2 Gene Ala55val Polymorphism and Sudden Sensorineural Hearing Loss

Abstract: OBJECTIVES:The pathology of sudden sensorineural hearing loss, which is known as sudden deafness (SD), remains unknown. The purpose of this study was to investigate the association between mitochondrial uncoupling protein 2 (UCP2) polymorphism and SD risk. MATERIALS and METHODS:We compared 83 patients suffering from SD and 2048 controls who participated in the Longitudinal Study of Aging at the National Institute for Longevity Sciences. Multiple logistic regression was used to calculate the odds ratios (ORs) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…28 Data in the current literature show that several genetic polymorphisms correlated with oxidative stress, inflammation, thrombosis, and blood vessel permeability are associated to SSNHL predisposition and development. 10,12,20,24,28,36,37,40,41 On the basis of this evidence, it could be hypothesized that genetic factors could play a role in maintaining the delicate balance between ROS and antioxidants, pro-inflammatory and anti-inflammatory factors, proaggregants, and antiaggregants; since the balance among these factors is important for the inner ear homeostasis, their disruption could be a factor contributing to the ISSNHL onset. Furthermore, a possible link between SSNHL and major cardiovascular diseases, such as stroke and myocardial infarction, has been previously highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Data in the current literature show that several genetic polymorphisms correlated with oxidative stress, inflammation, thrombosis, and blood vessel permeability are associated to SSNHL predisposition and development. 10,12,20,24,28,36,37,40,41 On the basis of this evidence, it could be hypothesized that genetic factors could play a role in maintaining the delicate balance between ROS and antioxidants, pro-inflammatory and anti-inflammatory factors, proaggregants, and antiaggregants; since the balance among these factors is important for the inner ear homeostasis, their disruption could be a factor contributing to the ISSNHL onset. Furthermore, a possible link between SSNHL and major cardiovascular diseases, such as stroke and myocardial infarction, has been previously highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Koide et al 37 reported a significant association between the mitochondrial uncoupling protein 2 (UCP2) polymorphism and the risk of SSNHL onset. UCP2 plays an important protective role against free radicals in the inner ear.…”
Section: Genetic Polymorphisms and Inner Ear Inflammation And/or Oxidative Stressmentioning
confidence: 99%
“…Keywords: epidemiological studies, hearing impairment, screening, questionnaire, chronic general somatic pathology _________________________________________________________________________________________________  ВВЕДЕНИЕ Исследования, посвященные сенсоневральной тугоухости (СНТ), занимают в настоящее время одно из ведущих направлений не только в оториноларингологической практике, но и в медицине в целом [1,2]. Это обусловлено негативной тенденцией к увеличению пациентов с патологией звуковоспринимающей части слухового анализатора [1,3,4], полиэтиологичностью и генетической детерминированностью заболевания [5][6][7], наличием большого количества общесоматических заболеваний, симтомокомплекс которых включает нарушения в слуховом анализаторе [7][8][9][10][11]. Выраженные нарушения слуха приводят к инвалидности и требуют больших финансово-экономических затрат со стороны как пациента, так и от государственных структур [11][12][13][14]16].…”
Section: Purposeunclassified
“…Indeed, UCP2 deficiency is associated with mitochondrial abnormalities and is implicated in hearing loss. 38,48,60 A study comparing 83 patients suffering from sudden sensorineural hearing loss to 2,048 controls in a Japanese population showed a significant association between UCP2 polymorphisms and sensorineural hearing loss. 38 In a separate study, UCP2 (G-866 A) polymorphism was found to contribute significant risk to age-related hearing loss.…”
Section: Protecting Mitochondriamentioning
confidence: 99%
“…38,48,60 A study comparing 83 patients suffering from sudden sensorineural hearing loss to 2,048 controls in a Japanese population showed a significant association between UCP2 polymorphisms and sensorineural hearing loss. 38 In a separate study, UCP2 (G-866 A) polymorphism was found to contribute significant risk to age-related hearing loss. 48 Vegetable compounds (e.g., berberine, curcumin, and capsaicin) or pharmaceutical drugs (e.g., fenofibrate) are shown to induce UCP2 expression in a variety of cell types.…”
Section: Protecting Mitochondriamentioning
confidence: 99%